Can unconditional cash assistance improve household welfare? QUAIDS model for food commodities in Indonesia. Issue 1 (31st December 2022) - Rasyid, Mohtar
ABSTRACT: Expenditure patterns can be taken into consideration in determining the type of government assistance. Without adequate information on household expenditure patterns, cash transfers may not be effective in improving welfare. This study aims to examine the expenditure patterns of households receiving cash assistance in Indonesia. The expenditure pattern is estimated using the Quadratic Almost Ideal Demand System (QUAIDS). Four groups of expenditure types for food were examined: rice, staple food, beverages, tobacco and alcoholic beverages. The result showed that the largest predicted expenditure is for the purchase of staple food. Income elasticity for staple food is relatively highest than all other types of food. On the other hand, the price elasticity of tobacco and alcoholic beverages is relatively inelastic (lowest) compared to other food products. These results indicate that the provision of cash transfers for poor households has the potential to increase household welfare through increasing staple food consumption.